Sirtuin 6 plays an oncogenic role and induces cell autophagy in esophageal cancer cells - Nan Huang; Zhiwei Liu; Jiabei Zhu; Zhongqi Cui; Yuguang Li; Yongchun Yu; Fenyong Sun; Qiuhui Pan; Qingyuan Yang (Tumor Biology, 2017)
Sirtuin 6, a member of sirtuin family, is generally regarded as a tumor suppressor as it participates in suppressing hypoxia-inducible factor 1α and MYC transcription activity by deacetylating H3K9 (histone H3 lysine 9) and H3K56 (histone H3 lysine) at promoters of target genes, leading to the aerobic glycolysis inhibition and cell growth suppression. However, its expression has recently been reported to be highly elevated in a series of tumors, including prostate cancer, breast cancer, and non–small cell lung cancer, indicating that sirtuin 6 plays dual roles in tumorigenicity in a cell/tumor type–specific manner. To our knowledge, the biological roles of sirtuin 6 in esophageal cancer cells have still been underestimated. In the study, data from quantitative reverse transcriptase polymerase chain reaction–based assays and immunohistochemical assays revealed that sirtuin 6 was remarkably overexpressed in esophageal squamous tumor tissues. Moreover, its upregulation was closely related with clinical features, such as gender, pathology, tumor–node–metastasis, and cell differentiation. Subsequently, the biological tests showed that it promoted cell proliferation and induced the expression of Bcl2, a key anti-apoptotic factor, in esophageal carcinoma cells. Moreover, using the ratio of LC3II/I, a widely recognized autophagy biomarker, we showed that it apparently induced cell autophagy, which was further confirmed by the autophagy flux assays. In addition, results from western blotting assays and immunoprecipitation assays displayed that sirtuin 6 specifically interacted with ULK1 and positively regulated its activity by inhibiting its upstream factor mammalian target of rapamycin activity. In summary, our studies shed insights into the crucial functions of sirtuin 6 in esophageal carcinoma cells and provide evidence supporting sirtuin 6–based personalized therapies in esophageal carcinoma cell patients.